iSense: a technology platform for cold atom based quantum technologies - Bongs, Kai; Malcolm, Jon; Ramelloo, Clemens; Zhu, Lingxiao; Boyer, Vincent; Valenzuela, Tristan; Maclean, Jessica; Piccardo-Selg, Anton; Mellor, Chris; Fernholz, Thomas; Fromhold, Mark; Krüger, Peter; et al. (2014)
A breakthrough in cold atom quantum technology is hindered by a bottleneck in the supporting technologies. We discuss a cold atom technology platform developed within the European iSense project, aiming at a gravimeter as demonstrator.